PERTUMBUHAN DAN TINGKAT KELANGSUNGAN HIDUP BENIH IKAN PATIN Pangasius sp. PADA SUHU YANG BERBEDA - Saepudin, Asep; Mustahal, Mustahal; Putra, Achmad Noerkhaerin (Pusat Unggulan Iptek Ketahanan Pangan Universitas Sultan Ageng Tirtayasa, 2021)
Temperature is one of the physical parameters that greatly influences the survival and growth of fish. This study aims to evaluate temperature effect on the growth and survival rate of catfish. Catfish with an average length of 1.54 cm and an average weight of 0.33 g were kept in the aquarium for 45 days. This study consisted of 3 different temperature treatments with 3 replications, namely: A (temperature of 26 oC), B (temperature of 30 oC) and C (temperature of 34 oC). The results showed that significantly (P<0.05) the highest LPS value was found in the 26 oC temperature treatment, which was 4.44%/day, followed by the 34 oC temperature treatment at 3.72%/day and the 30 oC temperature treatment. by 3.70%/day. There were no significant differences in absolute length growth parameters and survival rates between treatments.